Enhanced anti-hepatoma effect of a novel curcumin analog C086 via solid dispersion technology. (1st January 2020) - Deng, Yanping; Chen, Chun; Xiao, Zhifeng; Huang, Xiuwang; Xu, Jianhua
Abstract: The novel curcumin analog C086, previously identified as an oral novel heat shock protein 90 (Hsp90) inhibitor, was found to exhibit anti-hepatoma activity in vitro and in vivo . However, owing to its limited aqueous solubility, the usage of C086 in the clinical application was restricted. This research focused on the increase of the aqueous solubility and bioavailability of C086 via a solid dispersion preparation to improve its accumulation in the liver, which accordingly enhanced anti-hepatoma activity. C086-solid dispersion (C086-SD) was successfully prepared by using solvent evaporation technology. As compared with bulk compound, aqueous solubility obtained with the optimal formulation (C086/PVP k30:1/6 ( w/w )) was increased by 1.741 million-fold, and in the following oral administration experiment, bioavailability was found to be improved by an approximately 28-fold relative to C086-Suspension and accumulate preferably in the liver. Accordingly, C086-SD exhibited stronger potent anti-proliferative effects against liver cancer cell line (i.e. HepG2) than pure C086. Moreover, C086-SD was found to have an enhanced anti-hepatoma effect using the orthotopic hepatocellular carcinoma xenograft in BALB/C nude mice. The results above suggested the potential application of C086-SD in the treatment of liver cancer.